Перспективи реформування пенітенціарної системи України: досвід Фінляндії - Яцишин, Михайло Михайлович; Крисюк, Юрій Петрович; Yatsyshyn, Mykhailo M.; Krysiuk, Yurii P. (Громадська організація "Пенітенціарна асоціація України", 2018)
Проаналізовано досвід Фінляндської Республіки для можливого застосування у ході реформування пенітенціарної системи України. Наголошено на тому, що саме позбавлення волі не працює як засіб виправлення правопорушника, тобто функції профілактики в’язниця не виконує. Повторне вчинення злочинів вимагає спеціальних заходів щодо інтеграції колишніх правопорушників у суспільство.

The article analyzes the experience of the Republic of Finland for its possible further use in the course of reforming the penitentiary system of Ukraine. It is noted that the penitentiary system can be considered both in a narrow and broad sense. In a broad sense, the penitentiary system is a set of interrelated and interdependent state-legal means, methods and guarantees aimed at achieving the goals of criminal punishment in the activities of bodies and institutions for the execution of punishments; In the narrow sense, it is a system of bodies and institutions for the execution of sentences. Analysis of the current legislation suggests that our state is applying the second approach for understanding the penitentiary system, which somewhat narrows the prospects for improving the criminal situation as a whole. The study of the experience of penitentiary reforms makes it possible to talk about the existence of several factors that are significant for their success. This is not only the clarity of reform plans and consistency in their implementation. The attitude of society to the proposals for reform is also important. A public request for a strict attitude towards criminals provokes lawmakers to strengthen criminal law, and judges to harsher sentences. However, the punitive stereotypes of society can be overcomed or circumvent, as happened in Finland. After all, deprivation of liberty does not work as a means of correcting the offender, that is, the prison does not fulfill the function of prevention. Preventing re-commission of crimes requires special measures to integrate former offenders into society. The approach of Finland seems to be possible in Ukraine solely on the condition of ensuring the implementation of the indisputable principle of the inevitability of criminal responsibility for the commission of a crime both for ordinary citizens and for the “elite”. It was noted that the improvement of the quality and effectiveness of the implementation of state policy in the penitentiary sphere is inextricably linked with the implementation of the relevant requirements and standards recognized in the highly developed Western European world.
Perspectives for the reform of penalty system in Ukraine: experience of Finland
Keywords: пенітенціарна система; рівень інкарцерації; злочинність; покарання; медіація; penitentiary system; level of incerceration; crime; punishment; mediation